The wild east : a biography of the Great Smoky Mountains - Brown, Margaret Lynn (New perspectives on the history of the South., 2000)
"The Wild East explores the social, political, and environmental changes in the Great Smoky Mountains during the nineteenth and twentieth centuries. Although this national park is most often portrayed as a triumph of wilderness preservation, Margaret L. Brown concludes that the largest forested region in the eastern United States is actually a re-created wilderness, a product of restoration and even manipulation of the land." "In the 1970s, Brown writes, the Smokies faced many of the consequences of these management decisions. Major crises with brook trout, black bears, and exotic species pushed park officials toward a greater regard for ecology. At the same time, scientists trained during the environmental movement foraged through the land's history seeking to re-create the look of the landscape before human settlement. Park management continues to waffle between these shifting views of wilderness, negotiating the often contradictory mission of promoting tourism and ensuring preservation."--Jacket